I love my dad - Liberts, Jennifer, 1970-; Legramandi, Francesco; Matta, Gabriella (New York : Random House, 2017)
The Disney Princesses show their love for their dads.
Keywords: Fathers -- Juvenile fiction; Daughters -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Princesses -- Juvenile fiction; Princesses -- Fiction; Daughters; Fathers; Princesses; JUVENILE FICTION / Fairy Tales & Folklore; JUVENILE FICTION / Girls & Women; JUVENILE FICTION / Media Tie-In.; Readers (Publications); Fiction; Juvenile works; Readers (Publications)